2004
DOI: 10.1124/mol.65.6.1485
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Interaction of Tyrosine Kinase Inhibitors with the ABCG2 Multidrug Transporter

Abstract: Tyrosine kinase inhibitors (TKIs) are promising new agents for specific inhibition of malignant cell growth and metastasis formation. Because most of the TKIs have to reach an intracellular target, specific membrane transporters may significantly modulate their effectiveness. In addition, the hydrophobic TKIs may interact with so-called multidrug transporters and thus alter the cellular distribution of unrelated pharmacological agents. In the present work, we show that certain TKIs, already in the clinical pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
213
2
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(229 citation statements)
references
References 34 publications
11
213
2
3
Order By: Relevance
“…Oral gefitinib has been reported to increase the oral bioavailability of irinotecan and topotecan (6,13) and to enhance the central nervous system penetration of topotecan in mice (14). Other studies support the hypothesis that gefitinib is a substrate for BCRP (7,15,16) and a functional variant of ABCG2 (BCRP) has recently been associated with greater gefitinib accumulation in humans, thus supporting the hypothesis that BCRP expression and activity may affect the pharmacokinetics of gefitinib (16).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Oral gefitinib has been reported to increase the oral bioavailability of irinotecan and topotecan (6,13) and to enhance the central nervous system penetration of topotecan in mice (14). Other studies support the hypothesis that gefitinib is a substrate for BCRP (7,15,16) and a functional variant of ABCG2 (BCRP) has recently been associated with greater gefitinib accumulation in humans, thus supporting the hypothesis that BCRP expression and activity may affect the pharmacokinetics of gefitinib (16).…”
Section: Introductionmentioning
confidence: 82%
“…Gefitinib has been reported to inhibit BCRP and, to a lesser extent, P-gp function in vitro and in vivo (6,7). Gefitinib was able to reverse resistance and enhance cytotoxicity of well-known BCRP/P-gp substrates, such as topotecan, mitoxantrone, irinotecan, and its active metabolite SN-38, in BCRP-or P-gp-overexpressing cells (8 -12).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that imatinib interacts with the multidrug transporter proteins, MDR1 (multidrug resistance protein 1, also known as P-glycoprotein) [38][39][40] and MXR (multixenobiotic resistance protein, also known as breast-cancer resistance protein). [41][42][43] Increased expression of these two efflux proteins reduces intracellular concentrations of imatinib and decreases the antiproliferative effects of the drug. 40,41,[44][45][46] Furthermore, in a recent study of 90 imatinibtreated CML patients, single nucleotide polymorphisms in the gene encoding MDR1 seemed to affect both plasma concentrations of imatinib and clinical response to the drug.…”
Section: Intracellular Imatinib Concentrationsmentioning
confidence: 99%
“…Gefitinib inhibits ABCG2-dependent active drug extrusion, which mediates irinotecan efflux and protects cells from irinotecan toxicity (Wierdl et al, 2003;Ozvegy-Laczka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%